CORRELATION OF SYMBOLIC LANGUAGE AND CAUSE AND EFFECT RELATIONSHIP TO MATHEMATIC MODELING IN SENIOR HIGH SCHOOL PHYSICS LESSONS - Sari, Desy Kumala; Dinata, Pri Ariadi Cahya (Journal of Teaching and Learning Physics, 2022)
The generic science skills are the basic abilities that must be possessed by every student who studies science. This ability consists of various indicators namely direct observation, indirect observation, symbolic language, logical inference, causal relations, mathematical modeling, and construct concepts. This study only focused on indicators of symbolic language, causal relationships, and mathematical modeling. This research is a correlation study that aims to find out the relationship between symbolic language abilities and causal relationships on mathematical modeling abilities in physics subjects. The results of the study indicate that there is a relationship in the ‘sufficient’ category between symbolic language abilities and causal relationships to mathematical modeling abilities in physics subjects. Suggestions for further researchers are that in the learning process it should focus on the science process, which needs to guide students to develop their generic abilities in science, especially physics.